Impacts of tillage and nutrient management on soil porosity trends in dryland agriculture. (26th July 2021) - Mateo‐Marín, Noemí; Bosch‐Serra, Àngela D.; Molina, Maria G.; Poch, Rosa M.
Abstract: In dryland Mediterranean semi‐arid areas, the use of slurries and no‐till are encouraged to reduce costs. This paper evaluates the effect of such practices in terms of morphological changes of the topsoil porosity. The experiment had seven fertilization strategies (five of them including pig slurries applied at cereal sowing or at tillering) combined with no‐till or tillage by disc‐harrowing at sowing. Soil was classified as a Typic Xerofluvent. Texture was silt loam. Pores in the apparent pore diameter (APD) intervals higher than >15 μm and at intervals up to 400 μm were studied with a micromorphological approach plus image analysis. Fifty‐four undisturbed and surface soil samples (0.06 m deep) were analysed. Samples were collected in the third year after the establishment of tillage treatments and throughout the cereal growing season: just before tillage, at cereal tillering and at grain maturity. The incorporation of slurry at pre‐sowing (~2 Mg ha −1 of organic matter ha −1 ) enhanced porosity (>15 μm) by 33% in the cropping season but mainly in the 200–400‐μm class. Similar behaviour was observed in plots without topdressing fertilization, when till was compared with no‐till. Thus, the potential movement of water and nutrients due to bypass flow was increased. When slurries were only applied at cereal tillering, only the tillage treatment increased topsoil porosity at grain maturity in the 15–100‐μm class by 22% and, thus, increased those pores responsible for soil and water storage. Temporary changes in pore shape after tillage can be explained by microstructure collapse and compaction followed by a partial porosity recovery by faunal activity at grain maturity. Highlights: Slurry at pre‐sowing, combined with tillage, increases topsoil coarse pores Tillage increases mesoporosity at grain maturity regardless of the slurry fertilization strategy Pore shape changes after tillage are not further visible at grain maturity No‐till tends to compact silty topsoils, creating platy structures later counteracted by fauna